Horizontal Dip‐Spin Casting of aqueous alumina‐polyvinylpyrrolidone suspensions with chopped fiber. Issue 6 (8th June 2017) - Wiesner, Valerie; Acosta, Manuel; Rueschhoff, Lisa; Youngblood, Jeffrey; Trice, Rodney
Abstract: A novel ceramic processing method, called Horizontal Dip Spin Casting (HDSC), enabled fabrication of tubular ceramic parts with an aligned chopped fiber phase. HDSC was demonstrated using highly loaded aqueous alumina suspensions with >50 vol.% solids loading and ≤5 vol.% water‐soluble polymer employed as a rheological modifier. Chopped carbon fibers were added to the suspensions to attain maximum loadings of 30 vol.%. During forming, cylindrical foam molds were dipped into the suspension while being rotated radially about the long axis. Simultaneously, a doctor blade was placed at a specified distance from the foam surface to facilitate the flow of the suspension to align the fiber and control the thickness of the material that accrued on the mold. Rheological study of alumina‐PVP suspensions with and without chopped carbon fiber showed that the suspensions exhibited a yield‐pseudoplastic flow behavior. The degree of alignment of the carbon fiber phase in the green bodies was characterized for various suspension formulations, carbon fiber contents and forming speeds. Stereological characterization of green body specimens confirmed the effectiveness of HDSC to attain the desired tubular geometry with considerable fiber alignment for a suspension composition containing ≤20 vol.% chopped fibers.